Obim, struktura i strah od kriminaliteta u suburbanoj sredini (studija slučaja Općina Vogošća) - Kapo, Kenan (Kriminalističke teme, 2017)
Inspiracija za rad i problem(i) koji se radom oslovljava(ju): Suburbana područja kao predmet istraživanja su relativno slabo zastupljena u domaćoj literaturi. Uloga i povezanost zvaničnih podataka o kriminalitetu i onih dobivenih kriminološkim istraživanjima, a koji se bave srodnim fenomenima, kao što je strah od kriminaliteta, rijetko su istraživani. Ciljevi rada (naučni i/ili društveni): Opisati i objasniti povezanost stvarnih razina kriminaliteta mjerenih statistikama zvaničnih organa i alternativnih podataka o kriminalitetu. Metodologija/Dizajn: U radu je primijenjen klasični deskriptivni pristup u prikupljanju podataka dobivenih ispitivanjem. Za analizu obima i strukture kriminaliteta koristila se sekundarna analiza izvještaja o radu relevantnih organa. Ograničenja istraživanja/rada: Istraživanjem se nije vršila direktna komparacija sa stanjem kriminaliteta i strahom od kriminaliteta između suburbanih i urbanih sarajevskih općina, čime bi se pružili interesantni uvidi u moguće razlike. Margina pogreške od skoro 6 posto odražava se na preciznost i valjanost dobivenih rezultata. Rezultati/Nalazi: Tipičnu suburbanu općinu u Kantonu Sarajevo, Vogošću, ne opterećuje ista razina problema sa kriminalitetom kao što je to slučaj sa drugim općinama. Najznačajniji uticaj na strah od kriminaliteta stanovnika Općine Vogošća imaju neki korelati fizičke i društvene ranjivosti. Slaba prisutnost znakova fizičke i društvene dezorganizacije odražava se na niske razine straha od kriminaliteta. Generalni zaključak: Potencijal zajednice u prevenciji kriminaliteta ne smije se ignorisati. Potrebno je iskoristiti nalaze istraživanja za kreiranje adekvatnih programa prevencije. Opravdanost istraživanja/rada: Teorija susjedske kontrole, kao jedna od ekoloških teorija, u nekim svojim postavkama je testirana istraživanjem. Njene važnije tvrdnje o uticaju obilježja zajednice na stvarne razine kriminaliteta i strah od istoga su potvrđene. The Volume, Structure and Fear of Crime in Suburban Areas (Case Study Municipality Vogosca) Research paper inspiration and problem(s) addressed: Suburban areas as a subject of research are relatively poorly represented in domestic literature. The function and the connection between official criminality data and criminological investigations that deal with related phenomena, such as the fear of criminality, have rarely been investigated. Research paper objectives (scientific and/or social): Describe and explain the correlation of the actual levels of criminality measured by statistics of official bodies and alternative criminality data. Methodology/Design: A classic descriptive approach in the collection of data obtained by investigation was applied in this paper. The secondary analysis of the report on the work of the relevant bodies was used to analyze the scope and structure of criminality. Limitations of research/paper: The research did not include a direct comparison of the state of criminality and the fear of criminality between suburban and urban municipalities in Sarajevo, which would provide an interesting insight into possible differences. The margin of error of almost 6 percent is reflected on the precision and validity of the results obtained. Results/Findings: A typical suburban municipality in Sarajevo Canton, Vogošća, is not burdened by the same level of problems with criminality as is the case with other municipalities. The most significant impact on the fear of criminality of the residents of Vogošća municipality has some correlations of physical and social vulnerabilities. The low presence of physical and social disorganization signs reflects on low levels of fear of criminality. General Conclusion: The potential of the community in criminality prevention should not be ignored. Research findings should be used in the creation of adequate prevention programs. Justification of research /paper: The theory of neighbor control, as one of the ecological theories, has been tested by the research in some of its settings. Some of the most important statements of this theory on the influence of community features on the actual levels of criminality and the fear of it have been confirmed.